Call for participation: How the European Union attempts to respond to new societal challenges through engaging with Civil Society Organisations - Dabrowski de Flores, Bettina (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The changing social environment prompted the European Union (EU) to rethink its strategies towards its citizens. Phenomena such as distrust towards government institutions, nationalist movements and the alleged democratic deficit are the reasons why the EU aims at engaging with the civil society in its public policy, ranging from agenda setting to decision-making via instruments such as consultations. This paper intends to analyse the rationale behind implementing and pursuing this strategy. As the EU tries to increase its legitimacy, it needs to be evaluated if the EU meets the demands of citizens. For this analysis, a structured literature review will be conducted. This article desires to demonstrate that civil society organisations undergo processes of professionalization and transformation into providers of knowledge and expertise; therefore, ordinary citizens are not represented adequately in the EU via CSOs. Hence, the EU has desired to get closer to its citizens; however, with the current strategies the importance of membership has decreased and the opportunities for engagement have become more elitist. Further research is needed to evaluate the reasons behind this trend for the EU to draw appropriate conclusions and re-formulate its policy towards including its citizens.